Religion, Politics, and Turkey’s EU Accession
XIII, 231 p.
Keywords: This book brings together historians, political scientists, social anthropologists and legal scholars from Turkey and the EU. The authors address questions such as the role of religion in EU membership debates, religious parties in Turkey and Europe, religion and European security, freedom of religion and minority rights in Turkey and the EU.